Unravelling seismogenesis and characterizing the unique features of two significant felt earthquakes (M > 4.0) of 2020 in the southwestern parts of the Delhi region - Sanjay K. Prajapati; Ajeet P. Pandey; Sudipto Bhattacharjee; Shikha Vashisth; O. P. Mishra (Frontiers in Earth Science, 2024)
Two significant earthquakes (M4.6 and 4.2) occurred close to a NE–SW-trending lineament in the southwestern part of the Delhi NCR (National Capital Region) within a short time span of about 5 months in 2020. These events were located to the north of the Alwar district in Rajasthan and generated a significant ground shaking in and around Delhi. In the present study, we tried to understand a causal relationship between the events and a nearby source in the region, geologically demarcated as the lineament. We analyzed the broadband waveform data from 26 seismic stations that recorded the recent events of 03 July 2020 (M4.6) and 17 December 2020 (M4.2). Typically, the epicentral area has been devoid of significant earthquakes since the past six decades; however, a few minor events (M < 4.0) have been recorded till date. Analysis of the earthquake database for two decades (2000–2022) revealed low seismicity (nearly quiescent-like situation) in ∼100 sq km area around the epicentral zone, unlike considerable seismicity along faults/lineaments close to the Delhi region. The full-waveform inversion analyses of the events indicate normal faulting with a minor strike–slip components. The source parameters, viz., source radius, stress drop, and seismic moment, were estimated to be 6 km, 166 bars, and 8.28E+15 Nm, respectively, for the 03 July 2020 event and 4 km, 138 bars, and 2.29E+15 Nm, respectively, for the 17 December 2020 event. The causative source of these events is ascertained based on the stress inversion modeling that indicated a NW–SE tensile stress corroborating well with the NE–SW-trending lineament mapped in the study region. The static Coulomb stress modeling indicated that the event which occurred on 3 July 2020 had advanced the triggering process of the event in the northeast segment of the same source that occurred on 17 December 2020. We further emphasize that the aforementioned lineament probably activated due to the regional tectonics of the study area. The causative source of these events with strike 48°, dip 86°, and rake −60° is found to be in the conformity with the local tectonics and is well-supplemented by a high stress ratio (0.70 ± 0.05) and low friction coefficient (0.5).